PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) DAN MOTIVASI TERHADAP HASIL BELAJAR PKn SISWA DI SMP NEGERI 10 PALU - Mandiri, Djaya (Katalogis, 2020)
This research aims to figure out the differences between learning achivement of the students taught think pair share and students taught conventional learning; the diffrerence learning outcome between high and low motivated students. The sample of this research is VIII A grade consisted of 28 students as the control class. The disign of this research is quasi eksperimen 2 x 2. The treatment variable is learning model and the attribute variable is learning motivation, while the dependent varible is the learning achivement of civil education. The hypothesis was tested through ANAVA two ways with different cell to significant level of 5%. The result of the differences between think pair share model achievement and conventional proven by the score of statistic test whereÂ Fcounted = 7.084 and Ftable = 5.79 or H0 is rejected. It means that there is difference between learning achievement of think pair share class to the conventional class. The score of statistic test whereÂ Fcounted = 25.27 and Ftable = 5.79 or H0 is rejected. It means that there is difference between group of high motivated students and group of low motivated students.